FORBIDDEN IMMISIONS AND ENVIRONMENTAL PROTECTION - Popov, Danica (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
In the Serbian Law and in the most of jurisdictions, there are limits on excercising the right of property. A real estate owner must refrain from activities by which the use of other real estate is being impoded through the emission of exessive gasses, vapors, smoke, heat, noise, the draining of waste water, etc.Neighboring real estate ownwrs must endure such harmful effects if they do not exceed the limit of usual endurance, taking into account the nature and purpose of such real estate, as well as local conditions. The property owner who is affected by emissions exceeding the set limit, has the right to request a stop of emissions which exceeded the allowed volume of emissions. If  the emisions originate from  some industrial plants, within the activity allowed by a state autority, one cannot request a cessation of such activities, but can simply seek damages. The issue of the invironmental protection in the Republic of Serbia is regulated by a number of particular substantive laws, with a Law of environmental protection of 2009. as fundamental  Law.